Perancangan Aplikasi Enkripsi Kata Menggunakan Algoritma Playfair Cipher Berbasis Web - Pristiwanto, Muhammad (Journal of Computer Science and Information System(JCoInS), 2021)
In this day and age information/messages are not only sent by courier or traditionally but have been adapted to technological developments. One phenomenon that occurs because it involves internet technology in sending messages and exchanging data is the issue of wiretapping, counterfeiting and even theft of messages. Cryptography has a very important role in the era of digitalization which aims to secure information. Information that is privacy can be avoided from third persons and the information to be submitted can be protected. On the basis of this idea, it is necessary to create a medium or application that can be used to perform the encryption process and description of the message so that the message sent can be received by the recipient in a state of guaranteed legitimacy. This study uses the cryptographic algorithm Playfair Cipher. From the results of testing the application built, in the process of encryption and description, it can be proven to guarantee the security and confidentiality of messages.